A rare case of reversible constrictive pericarditis with severe pericardial thickening in a patient with adult onset Still's disease - Buß, Sebastian Johannes; Wolf, David Gregor; Mereles, Derliz; Blank, Norbert; Katus, Hugo; Hardt, Stefan (International journal of cardiology, 2010)
A 21-year-old male German patient, was referred to our intensive care unit from a peripheral hospital with severe septic illness and fever. The echocardiographic investigation revealed a massive pericardial thickening of at least 20 mm mainly located posterolateral and inferior, without typical pericardial effusion. An inspiratory diastolic septal shift to the left, as well as pathological respiratory PW-Doppler profiles of mitral and tricuspid inflow velocities could clearly been detected in the examination. The patient describes at the interview in our intensive care unit, that he has previously been well, without any symptoms of cardiac failure or joint pain. We diagnosed an adult onset Still's disease (AOSD). Thus, prednisone pulse-therapy was initiated with 250 mg and reduced stepwise in the following days. All the symptoms improved dramatically within a few days. The documented pericardial thickening showed a significant reduction to approximately 6 mm already after 4 days of therapy AOSD should not be forgotten in the differential diagnosis of pericardial disease due to its potentially life threatening complications. Usually, echocardiography reveals typical pericardial effusion. In this case the patient presented with an impressing, atypical thickening of the pericardium in the posterolateral region, hardly ever seen in AOSD.
Erstmals am 30. Januar 2009 online erschienen
Gesehen am 22.03.2023